Blacks in Superhero Comics - Weschenfelder, Gelson Vanderlei (2013)
This study addresses the representations of black people in comics under the perspective of historical context of black characters mainly in the superhero genre, through a bibliographical exploratory approach. In the first part, the article presents the context of the movement for rights for equality in the perspective of the US scenario, locus vivendi of the superhero comics. In the second part, the study presents the black characters and their representation in the adventure genre and the super adventure genre. At the end, the study indicates that the representation of black identity conquered space in the contemporary art-cultural production, initially motivated by a quota policy which revealed itself no longer necessary. The comics are thus the stage where sensitive questions can be debated, acting as promoter of social changes in this way.